Memórias das danças do marabaixo e do batuque: cultura quilombola e corporeidade na comunidade do Curiaú em Macapá-AP - Gomes, Francisco Marlon da Silva (2012)
The research was realized in the curiaú quilombola community, in Macapá city. The objective of this study is to comprehend what the marabaixo and batuque dance means to the quilombolas (descendant of slave who lives in the curiaú community). The interest in of the investigation appeared during a visit we did. We were there to take some picture and show the cultural habits of this community. So what we pretend through this observation is to know what marabaixo and batuque dance represents in their life. Why they dance marabaixo and batuque ?; when they dance?; how did they learn this dance?; what age is appropriate to start learn the dance? how is this dance important to the community?; what values it brings to the community?. Marabaixo and Batuque dancing is a resistance act, having the power to act and speak without restrictions, a corporeity of the black people quilombola. In the curiaú community the body is seen like movement, sensibility, subjectivity, culture and a way to preserve their histories and memories